The Effect of Variations in The Distance of the Expansion Valve with The Evaporator on the Performance of the Type Cooling Machine Split AC - Alfian, Handi; Wiratmaja, I Gede; Nugraha, I Nyoman Pasek (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2022)
This research was conducted with the aim of finding the effect of variations in the distance of the expansion valve with the evaporator on the performance of the type cooling machine Split AC. The method used in this research was the experimental method. The variation used in this research were the variation of the distance between the expansion valve and the evaporator by 1 meter, 2 meters, and 3 meters (standard), then the value sought in this study were the room cooling rate and COP (Coefficient of Performance). Data collection in this study was repeated 15 times. From the results of data collection and the calculation process, the room cooling rate has increased compared to the standard distance variation, which were 3 meters, where the highest room cooling rate occurs at a distance of 1 meter variation of 0.0876 Kj/s, so the smaller the expansion valve distance from the evaporator, the smaller the expansion valve distance from the evaporator. room cooling rate increases, and vice versa. And for the COP results from variations in the distance of the expansion valve with the evaporator decreased from the standard distance variation of 3 meters, where the lowest COP occurred at a distance variation of 1 meter by 33.58, so the smaller the distance of the expansion valve with the evaporator, the COP of the cooling machine decreased and vice versa.